Status Mutu Air Sungai Petanu Berdasarkan Perhitungan Metode Storet - Sastra Wibawa, I Made; Mahendra Dewi, Ni Luh Putu; Simeon Petrus Tallo (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2024)
The Petanu River is one of the rivers in Gianyar Regency. The use of the Petanu river is for irrigation of rice fields, holy places, waterfall tourism, as the main function of domestic lime disposal and there is illegal sandstone mining in several Petanu river basins. The Petanu River is also used for the community's basic needs, namely bathing, washing and toilets. Based on these activities, it will certainly affect the water quality of the Petanu river. Based on storet method calculations, the Petanu river experiences moderate pollution. This was influenced by the phosphate parameter at the monitoring location in the middle of the Petanu River which exceeded the class II water quality standard with a concentration of 0.3 mL. The fecal coliform parameters were found in the middle monitoring location with a concentration of 2,400 MPN/100 mL, the downstream monitoring location was 1,500 MPN/100 mL which exceeded the threshold for class II water quality standards.